An impregnation film-forming agent for preparing a concrete early surface impregnation anti-cracking agent, and a preparation method and application thereof

CN121471419BActive Publication Date: 2026-10-27江苏博思通新材料有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511476539.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-16
Publication Date
2026-10-27
Estimated Expiration
2045-10-16

AI Technical Summary

Technical Problem

[0004]除此之外市面上也有很多种类的抗裂剂在出售,但总结下来现有的浸渍防裂剂主要存在以下缺陷:1、裂缝敏感性:混凝土表面出现宽度超过0.2mm的裂缝时,水分会通过裂缝渗透,导致防裂剂失效‌

Benefits of technology

[0032]1. 本发明合成的浸渍成膜剂化合物与有机硅乳液有良好的互溶性,可以深入混凝土内部形成不同的交联网络,增强了渗入成膜的致密性和附着力,提高了外部涂层的阻隔性能,‌‌解决了工程领域混凝土表面早期过早失水导致的微裂纹产生的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121471419B_ABST
    Figure CN121471419B_ABST
Patent Text Reader

Abstract

The application discloses an impregnation film forming agent for preparing a concrete early surface impregnation anti-cracking agent and a preparation method and application thereof. The impregnation film forming agent is mainly prepared from glycidyl methacrylate and an unsaturated ester small monomer, and is obtained by performing a free radical polymerization reaction under the conditions of an initiator, a chain transfer agent and a reducing agent to obtain an epoxy group containing impregnation molecule, and then performing an epoxy ring opening reaction on the epoxy group containing impregnation molecule and an alcohol ester compound. The impregnation film forming agent can be used to prepare a concrete early surface impregnation anti-cracking agent. The impregnation anti-cracking agent with the structure can penetrate into capillary holes of concrete, chemically reacts with hydrated cement, and forms a polysiloxane interpenetrating network structure. The structure not only endows the concrete surface with long-term hydrophobicity, but also maintains the breathing and air permeability functions, effectively prevents water and harmful substances from invading, and thus significantly improves the durability of the concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of concrete impregnation crack prevention agents, specifically relating to an impregnation film-forming agent for preparing early-stage concrete surface impregnation crack prevention agents, its preparation method, and its application. Background Technology

[0002] Over the past few centuries, concrete construction has undergone tremendous changes. From ancient stone masonry to modern high-rise buildings, concrete, as a vital building material, has played an indispensable role in architectural history. From the invention of cement in the 19th century to modern precast concrete technology, technological innovation has driven the development of concrete construction. Concrete's strength, durability, and cost-effectiveness make it a crucial material in the global construction industry. However, concrete structures exposed to the outdoor environment for extended periods are indeed susceptible to various surface defects and performance degradation due to factors such as sun and rain, and porous structures. Cracks in concrete are among the most common defects, caused by shrinkage deformation due to factors like age, temperature, and humidity, or stress concentration due to external forces. Cracks lead to decreased strength and durability. Water seepage in cast-in-place concrete components is also prevalent, primarily due to the presence of micropores and cracks within the concrete. Water seepage not only corrodes concrete components but can also damage the building structure. In projects like harbors and cross-sea bridges, long-term exposure to salt spray and chloride ion corrosion environments makes traditional concrete prone to seepage cracking, leading to problems such as steel reinforcement corrosion. The lifespan of concrete is a core indicator of the durability of modern engineering projects, and how to avoid and reduce the aforementioned problems in concrete is an area that urgently needs research.

[0003] Existing reports on crack-resistant agents mainly focus on achieving superior performance through the compounding of organic emulsions or changes in application conditions. For example, patent CN120463441A discloses an internal curing agent for ultra-high performance concrete, which consists of a mixture A of 650-700 parts of functional polymers with slow-release components (sulfonic acid groups, amide groups, carboxylic acid groups, and ester groups); a water-retaining component B composed of a mixture of high-molecular water-retaining component B1 and surfactant-coated component B2; and a shrinkage-reducing component C composed of 50-150 parts of air-entraining agent, defoamer, and water. This effectively improves the problem of early shrinkage cracking in concrete. Some patents also compensate for concrete shrinkage through volume changes caused by the hydration of inorganic materials, thereby achieving crack prevention. For example, patent CN115043610A discloses a concrete crack-resistant agent whose preparation method involves the combined action of a composite expansion agent, a hydration heat inhibitor, an internal curing agent, short-cut fibers, and a composite impermeable agent in the concrete, which complement and promote each other, solving the problem of easy cracking in ordinary concrete. However, these anti-cracking agents are mainly admixtures introduced during the concrete mixing process, participating in the cement hydration process. Patent CN120519065 A discloses a concrete surface strengthening coating and concrete curing agent composed of epoxy ester resin, water, HEC cellulose, organosilicon emulsion, polyphosphate, dispersant, defoamer, mica, talc, heavy calcium carbonate, water-repellent agent, silicone resin emulsion, pure acrylic emulsion, film-forming aid, preservative, and thickener, which can significantly improve the surface strength and resistance to ion penetration of concrete. However, this is mainly achieved through the compounding of multiple organic emulsions, resulting in poor film-forming and penetration capabilities. Patent CN 104559682 A describes a water-based epoxy-acrylic self-stratifying emulsion for concrete surface protection, mainly prepared using the RAFT fine emulsion polymerization method to obtain an epoxy-acrylic emulsion. The epoxy emulsion, epoxy-acrylic emulsion, acrylic emulsion, and various additives are then formulated into a self-stratifying concrete protective agent. The main advantage is that epoxy resin automatically moves towards the substrate during the emulsion drying and film formation process, increasing its adhesion to the concrete surface and thus improving the concrete's resistance to carbonation, salt erosion, and impermeability. This is primarily achieved through surface film formation.

[0004] Besides these, many types of crack-resistant agents are available on the market, but in summary, existing impregnating crack-resistant agents mainly have the following defects: 1. Crack sensitivity: When cracks wider than 0.2mm appear on the concrete surface, moisture can penetrate through the cracks, causing the crack-resistant agent to fail. Ordinary silane impregnating agents and other materials have significant shortcomings in crack protection and need to be used in conjunction with crack repair techniques; 2. Limited penetration depth: Traditional impregnating agents can only penetrate to a depth of 3-5mm, which is difficult to cover the deep micro-crack network inside the concrete; 3. Cracking and spalling: Conventional products cause colloid shrinkage due to solvent evaporation, leading to cracking and collapse. Some crack-resistant and seepage-reducing agents may also exhibit local honeycomb defects due to improper proportioning or uneven mixing; 4. Discoloration and aging: Epoxy resin materials are prone to reacting with oxygen to produce yellowing, affecting aesthetics. Traditional waterproof coatings also have problems with poor vapor permeability and easy oxidative degradation. These application defects limit the widespread use of crack-resistant agents in concrete engineering. Summary of the Invention

[0005] Objective of the Invention: To address the problems existing in the prior art, the objective of this invention is to provide an impregnation film-forming agent for preparing an early-stage concrete surface impregnation anti-cracking agent, its preparation method, and its application. This invention first involves a free radical polymerization reaction of glycidyl methacrylate with unsaturated ester monomers to obtain epoxy-containing impregnated molecules. Then, these epoxy-containing impregnated molecules undergo an epoxy ring-opening reaction with alcohol ester compounds to obtain an impregnation film-forming agent. Finally, by compounding this agent with styrene-acrylic emulsion, silicone emulsion, dimethyl phthalate, n-octanol, and an antifoaming agent, an early-stage concrete surface impregnation anti-cracking agent is obtained. This type of impregnation anti-cracking agent can deeply penetrate into the capillaries of concrete, reacting chemically with hydrated cement to form a polysiloxane interpenetrating network structure. This structure not only imparts long-term hydrophobicity to the concrete surface but also maintains its breathability, effectively preventing the intrusion of moisture and harmful substances, thereby significantly improving the durability of concrete.

[0006] Technical Solution: To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows:

[0007] In a first aspect, the present invention provides an impregnation film-forming agent, which is mainly composed of glycidyl methacrylate and unsaturated ester monomers, which undergo a free radical polymerization reaction in the presence of an initiator, a chain transfer agent and a reducing agent to obtain epoxy-containing impregnated molecules, and then the epoxy-containing impregnated molecules are reacted with alcohol ester compounds to undergo an epoxy ring-opening reaction.

[0008] The molecular structure of the impregnation film-forming agent is shown below:

[0009]

[0010] In this context, R1 is an alkyl group or a hydrogen atom, and R2 is an alkyl group.

[0011] As a specific implementation, the unsaturated ester monomers are selected from one or a combination of several of hydroxyethyl methacrylate, hydroxypropyl methacrylate, ethyl methacrylate, butyl methacrylate, hydroxyethyl acrylate, and hydroxypropyl acrylate.

[0012] As a specific implementation, the initiator is one or a combination of several of ammonium persulfate, sodium persulfate, potassium persulfate, or azobisisobutyronitrile; the reducing agent is one or a combination of several of sodium formaldehyde sulfoxylate, L-ascorbic acid, sodium bisulfite, ferrous sulfate, and Brügmann E51; the chain transfer agent is one or a combination of several of sodium hypophosphite, 2-mercaptopropionic acid, 3-mercaptopropionic acid, mercaptoacetic acid, and mercaptoethanol; and the alcohol ester compound is selected from dodecyl alcohol esters.

[0013] Secondly, the present invention provides a method for preparing the aforementioned impregnation film-forming agent, comprising the following steps:

[0014] (1) Add unsaturated ester monomers, initiator, chain transfer agent and reducing agent to glycidyl methacrylate, and carry out free radical polymerization reaction at 20℃-70℃ for 120-240 min to obtain epoxy-impregnated molecules.

[0015] (2) Dehydrate the reaction solution obtained in step (1), add catalyst and alcohol ester compound, carry out epoxy ring-opening reaction at 110℃-130℃ for 40-70 min, dilute, and obtain the impregnation film-forming agent.

[0016] As a specific implementation scheme, the molar ratio of glycidyl methacrylate, unsaturated ester monomers, initiator, chain transfer agent, reducing agent and alcohol ester compound is 1.0:(1.0~1.2):(0.05~0.3):(0.05~0.3):(0.01~0.1):(1.0~1.2).

[0017] As a specific implementation plan, in step (2), the catalyst is a NaOH solution with a concentration of 0.3%-0.4%.

[0018] Thirdly, the present invention provides the application of the impregnation film-forming agent in the preparation of an early-stage surface impregnation crack-resistant agent for concrete.

[0019] Fourthly, the present invention provides an early-stage concrete surface impregnation crack prevention agent, wherein the early-stage concrete surface impregnation crack prevention agent includes the above-mentioned impregnation film-forming agent.

[0020] As a specific implementation scheme, the early-stage concrete surface impregnation crack-preventing agent comprises the following components in parts by weight:

[0021] Impregnation film-forming agent: 10-20 parts

[0022] Styrene-acrylic emulsion: 40-60 parts

[0023] Silicone emulsion: 5-15 parts

[0024] Dimethyl phthalate: 5-10 parts

[0025] Octyl alcohol: 3-5 parts

[0026] Defoamer: 0.5-2 parts

[0027] Water: 0-16.5 parts.

[0028] Preferably, the defoamer is an organosilicone defoamer.

[0029] Fifthly, the present invention provides a method for preparing an early-stage concrete surface impregnation crack-preventing agent, comprising the following steps:

[0030] The above-mentioned impregnation film-forming agent is compounded with styrene-acrylic emulsion, silicone emulsion, dimethyl phthalate, n-octanol, defoamer and water, and stirred at 100-300 rpm for 40-60 minutes to obtain the final product.

[0031] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0032] 1. The impregnation film-forming agent compound synthesized in this invention has good miscibility with organosilicon emulsion, and can penetrate deep into the concrete to form different cross-linked networks, thereby enhancing the density and adhesion of the penetrated film, improving the barrier performance of the external coating, and solving the problem of microcracks caused by premature water loss on the concrete surface in the engineering field.

[0033] 2. The concrete early-stage surface impregnation crack-preventing agent of the present invention exhibits a contact angle greater than 90° with water after forming a film on the concrete surface, indicating that the externally formed coating film surface is hydrophobic. It provides strong shielding against corrosive substances in water, effectively preventing such substances from penetrating the concrete interior and achieving long-term protection of the concrete structure.

[0034] 3. The concrete early-stage surface impregnation anti-cracking agent of the present invention has a stronger adsorption effect on the surface of positively charged cement particles, and can penetrate into the concrete to a depth of more than 10mm to undergo hydrolysis-condensation reaction with alkaline substances in the concrete to generate hydrophobic siloxane (-Si-O-Si-) networks or polymer chains, which fill capillary pores and microcracks.

[0035] 4. The concrete early-stage surface impregnation anti-cracking agent of the present invention can rapidly lose water on the surface of concrete structures and react with hydroxyl groups to form a monolayer hydrophobic film that can block the intrusion of liquid water, chloride ions (reducing permeability by more than 90%) and CO2, delay carbonization and steel corrosion, and improve the durability of concrete structures.

[0036] 5. The method of this invention provides a new approach for preparing novel functionalized crack-resistant agents through redox soap-free emulsion polymerization and the chemical reaction of epoxy ring-opening.

[0037] 6. The raw materials used in the method of the present invention are abundant, and each step has been industrialized, making the method mature.

[0038] 7. The concrete early-stage surface impregnation crack-preventing agent prepared by the method of the present invention has stable performance after being prepared into an aqueous solution, does not separate or precipitate during storage, and is convenient to transport. Attached Figure Description

[0039] Figure 1 Comparison of boards coated with and uncoated with anti-cracking agent.

[0040] Figure 2 Comparison of cracks between those coated with and those not coated with anti-cracking agent. Detailed Implementation

[0041] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0042] Example 1

[0043] S1: At 70℃ with ethanol as solvent, 1 mol of hydroxyethyl methacrylate, 0.05 mol of ammonium persulfate, 0.1 mol of 3-mercaptopropionic acid and 0.02 mol of L-ascorbic acid were added to 1 mol of glycidyl methacrylate and subjected to free radical polymerization for 120 min to obtain hydroxyethyl methacrylate-type epoxy-impregnated molecules. Then, at 130℃, nitrogen gas was introduced for purging and dehydration. 0.4% NaOH catalyst and 1.2 mol of dodecyl alcohol ester were added to carry out epoxy ring-opening reaction for 70 min. Water was added to dilute to a 50% concentration of impregnation film-forming agent.

[0044] S2: Select 10 parts of the impregnation film-forming agent obtained in S1 and mix it with 60 parts of styrene-acrylic emulsion, 5 parts of organosilicon emulsion, 5 parts of dimethyl phthalate, 5 parts of n-octanol, 1 part of defoamer and 14 parts of water. Stir at 100 rpm for 60 minutes to obtain hydroxyethyl methacrylate type concrete early surface impregnation crack prevention agent.

[0045] Example 2

[0046] S1: At 20°C, using ethanol as a solvent, 1.2 mol of hydroxypropyl methacrylate, 0.15 mol of sodium persulfate, 0.1 mol of mercaptoacetic acid, and 0.1 mol of sodium bisulfite were added to 1 mol of glycidyl methacrylate, and a free radical polymerization reaction was carried out for 240 min to obtain hydroxypropyl methacrylate-type epoxy-impregnated molecules. Then, at 110°C, nitrogen gas was introduced for purging and dehydration. 0.4% NaOH catalyst and 1.1 mol of dodecyl alcohol ester were added for epoxy ring-opening reaction for 40 min. Water was added to dilute to a 40% concentration of impregnation film-forming agent.

[0047] S2: Select 20 parts of the impregnation film-forming agent obtained in S1, 40 parts of styrene-acrylic emulsion, 15 parts of organosilicon emulsion, 5 parts of dimethyl phthalate, 3 parts of n-octanol, 0.5 parts of organosilicon defoamer, and 16.5 parts of water for compounding. Stir at 300 rpm for 40 minutes to obtain hydroxypropyl methacrylate type - early surface impregnation crack prevention agent for concrete.

[0048] Example 3

[0049] S1: At 50°C, using ethanol as a solvent, 1.1 mol of butyl methacrylate, 0.15 mol of potassium persulfate, 0.05 mol of mercaptoethanol, 0.01 mol of Brügmann E51, and 0.001 mol of ferrous sulfate were added to 1 mol of glycidyl methacrylate, and a free radical polymerization reaction was carried out for 200 min to obtain butyl methacrylate-type epoxy-impregnated molecules. Then, at 115°C, nitrogen gas was introduced for purging and dehydration. 0.4% NaOH catalyst and 1.0 mol of dodecyl alcohol ester were added for epoxy ring-opening reaction for 55 min. Water was added to dilute to a 45% concentration of impregnation film-forming agent.

[0050] S2: Select 15 parts of the impregnation film-forming agent obtained in S1, 45 parts of styrene-acrylic emulsion, 10 parts of organosilicon emulsion, 10 parts of dimethyl phthalate, 5 parts of n-octanol, 2 parts of organosilicon defoamer and 13 parts of water and mix them together. Stir at 200 rpm for 50 min to obtain butyl methacrylate type - early surface impregnation crack prevention agent for concrete.

[0051] Example 4

[0052] S1: At 70℃ with ethanol as solvent, 1.1 mol of hydroxypropyl acrylate, 0.3 mol of azobisisobutyronitrile, 0.3 mol of sodium hypophosphite, and 0.01 mol of sodium formaldehyde sulfoxylate were added to 1 mol of glycidyl methacrylate and subjected to free radical polymerization for 180 min to obtain hydroxypropyl acrylate-type epoxy-impregnated molecules. Then, at 125℃, nitrogen gas was introduced for purging and dehydration. 0.4% NaOH catalyst and 1.05 mol of dodecyl alcohol ester were added to carry out epoxy ring-opening reaction for 60 min. Water was added to dilute to a 40% concentration of impregnation film-forming agent.

[0053] S2: Select 12 parts of the impregnation film-forming agent obtained in S1 and mix it with 55 parts of styrene-acrylic emulsion, 13 parts of organosilicon emulsion, 8 parts of dimethyl phthalate, 4 parts of n-octanol, 1 part of organosilicon defoamer and 7 parts of water. Stir at 200 rpm for 50 min to obtain butyl methacrylate type - early surface impregnation crack prevention agent for concrete.

[0054] Example 5

[0055] S1: At 70℃ with ethanol as solvent, 1.1 mol of hydroxypropyl acrylate, 0.1 mol of ammonium persulfate, 0.05 mol of sodium persulfate, 0.05 mol of 2-mercaptopropionic acid, 0.1 mol of mercaptoacetic acid, and 0.01 mol of sodium formaldehyde sulfoxylate were added to 1 mol of glycidyl methacrylate and subjected to free radical polymerization for 140 min to obtain hydroxypropyl acrylate-type epoxy-impregnated molecules. Then, at 125℃, nitrogen gas was introduced for purging and dehydration. 0.4% NaOH catalyst and 1.1 mol of dodecyl alcohol ester were added to carry out epoxy ring-opening reaction for 60 min. Water was added to dilute to a 45% concentration of impregnation film-forming agent.

[0056] S2: Select 20 parts of the impregnation film-forming agent obtained in S1 and mix it with 40 parts of styrene-acrylic emulsion, 15 parts of organosilicon emulsion, 5 parts of dimethyl phthalate, 3 parts of n-octanol, 0.5 parts of organosilicon defoamer and 16.5 parts of water. Stir at 250 rpm for 55 minutes to obtain hydroxypropyl acrylate type - early surface impregnation crack prevention agent for concrete.

[0057] Example 6

[0058] S1: At 20°C, using ethanol as a solvent, 1.0 mol of hydroxypropyl methacrylate, 0.1 mol of ammonium persulfate, 0.1 mol of potassium persulfate, 0.1 mol of mercaptoethanol, and 0.1 mol of sodium bisulfite were added to 1 mol of glycidyl methacrylate, and a free radical polymerization reaction was carried out for 220 min to obtain hydroxypropyl methacrylate-type epoxy-impregnated molecules. Then, at 125°C, nitrogen gas was introduced for purging and dehydration. 0.4% NaOH catalyst and 1.1 mol of dodecyl alcohol ester were added to carry out an epoxy ring-opening reaction for 60 min. The mixture was then diluted with water to a 30% concentration of impregnation film-forming agent.

[0059] S2: Select 20 parts of the impregnation film-forming agent obtained in S1 and mix it with 55 parts of styrene-acrylic emulsion, 13 parts of organosilicon emulsion, 8 parts of dimethyl phthalate, 3 parts of n-octanol, 1 part of organosilicon defoamer and 0 parts of water. Stir at 300 rpm for 40 minutes to obtain hydroxypropyl methacrylate type - early surface impregnation crack prevention agent for concrete.

[0060] Examples 1-6: Commercially available high-quality Sika H80 waterproof coating and epoxy resin (EP) were tested for carbonation depth according to JG / T335-2011 "Film-forming Coatings for Concrete Structure Protection", and for chloride ion penetration resistance and adhesion according to JT / T 695-2007 "Technical Conditions for Corrosion Protection Coatings on the Surface of Concrete Bridge Structures". The hydrophobicity was tested based on the contact angle between water droplets and the sample surface. The concrete mix proportions for the tests are shown in Table 1, and the test results are shown in Table 2.

[0061] Table 1. Mix Proportions for C60 Concrete

[0062]

[0063] Table 2 Test results of Examples 1-6 and external samples

[0064]

[0065] The results above demonstrate that, firstly, the product of this invention forms a monolayer hydrophobic film on the concrete surface, which can block liquid water, reduce chloride ion permeability and CO2 intrusion by more than 90%, and reduce the carbonation layer. Secondly, this invention has a stronger adsorption effect on the surface of positively charged cement particles, penetrating to a depth of more than 10 mm into the concrete to undergo hydrolysis-condensation reactions with alkaline substances in the concrete, generating hydrophobic siloxane (-Si-O-Si-) networks or polymer chains, filling capillary pores and microcracks. Thirdly, the contact angle between the film formed on the concrete surface and water is greater than 90°, indicating that the surface of the externally formed coating film is hydrophobic. Finally, this invention can penetrate deep into the concrete to form different cross-linked networks, enhancing the density and adhesion of the penetrated film, improving the barrier performance of the external coating, and solving the problem of microcracks caused by premature water loss on the concrete surface in engineering fields.

[0066] The embodiments of the present invention have been described in detail above with reference to specific examples. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.

Claims

1. An impregnation film-forming agent, characterized in that, The impregnation film-forming agent is prepared by free radical polymerization of glycidyl methacrylate and unsaturated ester monomers in the presence of an initiator, chain transfer agent, and reducing agent to obtain epoxy-containing impregnated molecules, and then performing an epoxy ring-opening reaction between the epoxy-containing impregnated molecules and alcohol ester compounds. The unsaturated ester monomers are selected from one or a combination of several of hydroxyethyl methacrylate, hydroxypropyl methacrylate, ethyl methacrylate, butyl methacrylate, hydroxyethyl acrylate, and hydroxypropyl acrylate. The initiator is one or a combination of several of ammonium persulfate, sodium persulfate, and potassium persulfate. The alcohol ester compounds are selected from dodecyl alcohol esters. The molar ratio of glycidyl methacrylate, unsaturated ester monomers, initiator, chain transfer agent, reducing agent, and alcohol ester compounds is 1.0:(1.0~1.2):(0.05~0.3):(0.05~0.3):(0.01~0.1):(1.0~1.2).

2. The impregnation film-forming agent according to claim 1, characterized in that, The reducing agent is one or a combination of several of sodium formaldehyde sulfoxylate, L-ascorbic acid, sodium bisulfite, ferrous sulfate, and Brügmann E51; the chain transfer agent is one or a combination of several of sodium hypophosphite, 2-mercaptopropionic acid, 3-mercaptopropionic acid, mercaptoacetic acid, and mercaptoethanol.

3. The method for preparing the impregnation film-forming agent according to any one of claims 1-2, characterized in that, Includes the following steps: (1) Add unsaturated ester monomers, initiator, chain transfer agent and reducing agent to glycidyl methacrylate, and carry out free radical polymerization reaction at 20℃-70℃ for 120-240 min to obtain epoxy-impregnated molecules. (2) Dehydrate the reaction solution obtained in step (1), add catalyst and alcohol ester compound, carry out epoxy ring-opening reaction at 110℃-130℃ for 40-70 min, dilute, and obtain the impregnation film-forming agent.

4. The method for preparing the impregnation film-forming agent according to claim 3, characterized in that, The molar ratio of the glycidyl methacrylate, unsaturated ester monomers, initiator, chain transfer agent, reducing agent, and alcohol ester compound is 1.0:(1.0~1.2):(0.05~0.3):(0.05~0.3):(0.01~0.1):(1.0~1.2).

5. The method for preparing the impregnation film-forming agent according to claim 3, characterized in that, In step (2), the catalyst is a NaOH solution with a concentration of 0.3%-0.4%.

6. The application of the impregnation film-forming agent according to any one of claims 1-2 in the preparation of an early-stage surface impregnation crack-resistant agent for concrete.

7. A concrete early-stage surface impregnation crack-preventing agent, characterized in that, The concrete early surface impregnation crack prevention agent includes the impregnation film-forming agent as described in any one of claims 1-2.

8. The concrete early-stage surface impregnation crack-preventing agent according to claim 7, characterized in that, The concrete early surface impregnation crack prevention agent comprises the following components in parts by weight: Impregnation film-forming agent: 10-20 parts Styrene-acrylic emulsion: 40-60 parts Silicone emulsion: 5-15 parts Dimethyl phthalate: 5-10 parts Octyl alcohol: 3-5 parts Defoamer: 0.5-2 parts Water: 0-16.5 parts.

9. A method for preparing an early-stage surface impregnation crack-preventing agent for concrete, characterized in that, Includes the following steps: The impregnation film-forming agent according to any one of claims 1-2 is compounded with styrene-acrylic emulsion, organosilicon emulsion, dimethyl phthalate, n-octanol, defoamer and water, and stirred at 100-300 rpm for 40-60 min to obtain the final product.

Citation Information

Patent Citations

  • Waterborne epoxy-acrylic acid self-layering emulsion for protecting concrete surfaces

    CN104559682A

  • Internal curing agent for ultra-high performance concrete and preparation method of internal curing agent

    CN120463441A

  • Concrete surface reinforcing coating and concrete curing agent

    CN120519065A

  • High-efficient curing agent for preventing cracking of concrete, as well as preparation method and application thereof

    CN106186794A

  • Penetration reinforced concrete interface agent, preparation method and application thereof

    CN115820053A